Ability of Lactococcus lactis To Export Viral Capsid Antigens: a Crucial Step for Development of Live Vaccines - Dieye, Yakhya (American Society for Microbiology, 2003)
Thefood grade bacterium Lactococcus lactis is a potential vehicle for protein delivery in the gastrointestinal tract. As a model, we constructed lactococcal strains producing antigens of infectious bursal disease virus (IBDV). IBDV infects chickens and causes depletion of B-lymphoid cells in the bursa of Fabricius and subsequent immunosuppression, morbidity, or acute mortality. The two major IBDV antigens, i.e., VP2 and VP3, that form the viral capsid were expressed and targeted to the cytoplasm, the cell wall, or the extracellular compartment of L. lactis. Whereas VP3 was successfully targeted to the three compartments by the use of relevant expression and export vectors, VP2 was recalcitrant to export, thus confirming the difficulty of translocating naturally nonsecreted proteins across the bacterial membrane. This defect could be partly overcome by fusing VP2 to a naturally secreted protein (the staphylococcal nuclease Nuc) that carried VP2 through the membrane. Lactococcal strains producing Nuc-VP2 and VP3 in various bacterial compartments were administered orally to chickens. The chickens did not develop any detectable immune response against VP2 and VP3 but did exhibit an immune response against Nuc when Nuc-VP2 was anchored to the cell wall of lactococci.